Uso de los minerales en la producción de ganado para carne. - Murillo Sánchez, Luis Felipe (2022)
The global demand for ever-increasing food production, coupled with modernization and accelerated progress in agricultural development today. Most of the grasses are not capable of satisfactorily supplying the essential nutrients for the good productive and reproductive performance of bovines. Minerals are essential components of diets and are beneficial for the growth, development and health of animals. The objective of this research was to know the use of minerals and the productive, reproductive yields in the production of cattle for meat. The research was qualitative, quantitative and analytical, the same that was based on the collection of information from books, data from magazines, scientific articles and web pages. Among the representative breeds of the Bos Indicus species, also known as Zebu cattle, it is more popular among tropical countries in which Bos indicus animals have been crossed with Creole animals or Bos Taurus Brahman, Nelore, Guzerat, Gyr, Indubrasil. The serum levels of Ca, P and Mg and the Ca:P ratio are not affected by the number of parities and there is a positive and significant correlation between the level of production with calcium levels. America the practice of substituting common salt for a complete mineral supplement. It is advisable to supply between 50 to 80 grams of mineral salt/animal/day. The calving percentages had increases from 10 to 50%, the abortions decreased from 10% to 1%. They demonstrated how mineral supplementation increased weight gains in heifers, in addition to increasing pregnancies and reducing the calving-conception interval and the number of abortions.